Student Perceptions of the Prospects of the Geography Education Study Program - Rajak, Rizal; Ismail, Hadijah (Journal of Social Knowledge Education (JSKE), 2024)
Purpose of the study: The aim of this research is to describe students' perceptions of the prospects of the Geophysical Education Study Program. Methodology: The method used in this research is descriptive qualitative. To obtain the desired data and in accordance with the interests of research explanation, the author used data collection techniques through questionnaire instruments and the techniques used in analyzing the data were in the form of percentages. Main Findings: Based on the results of the analysis in this research, the following were found: (1) the indicators of student views of the Geography Education Study Program are in the high category, (2) indicators of student responses regarding the Prospects of the Geography Education Study Program are in the medium category, (3) indicators The Geography Education Study Program students feel that they are in the high category in terms of study program development, which is good at providing education and learning, producing quality graduates, as well as developing the professionalism of internal human resources in order to produce superior and reliable figures. Novelty/Originality of this study: This research can be useful for the Geography Education Study Program, namely as information in the development of the Geography Education Study Program and as literature for further research, especially those related to the development of the Geography Education Study Program.